2022
DOI: 10.1021/acsanm.2c02734
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron-Sputtered Niobium Nanoparticles for Molecular Imaging of Brain Tissues through Surface-Assisted Laser Desorption/Ionization Mass Spectrometry

Abstract: Precise molecular identification of specific biomarkers in biological tissues is essential for accurate diagnostics of various diseases, injuries, and other clinically relevant issues. Surface-assisted laser desorption/ionization mass spectrometry imaging (SALDI MSI) has emerged as a powerful tool for biochemical analysis, particularly using noble-metal nanoparticle (NP) matrices. These are often, but not always, synthesized using wet chemistry approaches. Here, we report on NPs of naturally monoisotopic niobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…porous silicon [ 8 , 9 ], carbon-based materials [ 10 12 ], metal oxides [ 13 16 ], metal-organic frameworks [ 17 , 18 ], and metal nanomaterials [ 19 , 20 ]) several techniques have been developed for the fabrication of SALDI nano-matrices. The efficacy of these nano-matrices has been extensively demonstrated in several applications of SALDI-MS. For instance, Pleskunov et al reported niobium nanoparticles based SALDI-MS method for multiple phospholipids analysis on mouse brain tissue [ 21 ]. Minhas et al prepared nanostructured silicon SALDI-MS to detect anabolic doping agents and their metabolites in saliva and urine [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…porous silicon [ 8 , 9 ], carbon-based materials [ 10 12 ], metal oxides [ 13 16 ], metal-organic frameworks [ 17 , 18 ], and metal nanomaterials [ 19 , 20 ]) several techniques have been developed for the fabrication of SALDI nano-matrices. The efficacy of these nano-matrices has been extensively demonstrated in several applications of SALDI-MS. For instance, Pleskunov et al reported niobium nanoparticles based SALDI-MS method for multiple phospholipids analysis on mouse brain tissue [ 21 ]. Minhas et al prepared nanostructured silicon SALDI-MS to detect anabolic doping agents and their metabolites in saliva and urine [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 For gas-aggregated metal NPs, the formation of a cubic or spherical shape is governed by an interplay between the rate of arrival of metal atoms on the surface of a growing particle and the surface diffusion. 61 Both parameters dynamically change as the NPs thermalize from the close-to-melting point temperature near the magnetron to the ambient temperature at farther distances via collisions with Ar atoms. In the case of reactive sputtering, a high metal-to-nitrogen bond enthalpy provides an additional channel for the energy gain by the NPs, and it can be assumed that the thermalization of NPs proceeds slower, providing close-to-equilibrium conditions for atomic rearrangements and crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Metallic Hf and HfN NPs were synthesized using a custom‐built magnetron‐based gas aggregation cluster source (GAS, schematically shown in Figure S1a, Supporting Information) mounted onto a deposition chamber. [ 32,66–70 ] The metallic Hf NPs were synthesized in an argon (Ar) atmosphere, while the HfN NPs were prepared by adding nitrogen to Ar. The magnetron operated in constant current mode at 500 mA throughout all experiments.…”
Section: Methodsmentioning
confidence: 99%